EFFECT OF ETHYL METHANE SULPHONATE ON IMPROVING THE PHYSIOLOGICAL AND BIOCHEMICAL PROPERTIES OF TWO STRAWBERRY CULTIVARS - R. E. Y. AL-Hayali; S. I. Neamah (مجلة الأنبار للعلوم الزراعية, 2025)
A study was conducted in the laboratory of plant tissue culture in the College of Agriculture / University of Anbar to determine the effect of four concentrations of ethyl methane sulfonate (EMS) 0, 1, 2 and 3% on the biochemical characteristics of two cultivars of Albion and Rubjem under three levels of water stress using four levels of 0, 3, 6 and 9% of polyethylene glycol (PEG-6000). A factorial experiment was carried out using ten replicates according to CRD design. Albion cultivar plants treated with 9.0% PEG and 3.0% EMS concentration recorded the highest average APX enzyme activity of 0.5033 mmol min-1 mg-1 and CAT enzyme activity of 21.067 mmol min-1. The treatment of Albion cultivar plants with 9.0% PEG and 1.0% EMS concentration recorded the highest average for each of the iron contents, which reached 53.80 mg g-1 DW. Albion cultivar also achieved the highest average for GPX activity, which reached 0.160 mmol min-1 mg-1 under the level of 9.0% PEG and 2.0% EMS concentration. While the same cultivar Rubigim recorded the lowest significant reduction in H2O2 content at the two concentrations of 3.0% PEG and 3.0% EMS, which reached 0.540 µg g-1 FW. While the treatment with 3.0% EMS and 3.0% PEG concentrations for the same cultivar showed the highest average for the content of the amino acid proline, which reached 2.90 µg g-1